Marketing Strategy in the Admission of New Learners at SMPN 8 Tanjungbalai - Hendra, Hendra; Shopiana, Shopiana (ALACRITY : Journal of Education, 2025)
The purpose of this study was to evaluate the marketing strategies used to accept new students at SMPN 8 Tanjungbalai. The researcher used qualitative research. The data sources in this study consist of two categories: primary and secondary. The results showed that PPDB activities at SMPN 8 Tanjungbalai are strongly influenced by marketing strategy planning. The principal and the school marketing team are all involved in planning. In PPDB at SMPN 8 Tanjungbalai, the planning of marketing activities includes creating a committee structure, determining work programs, implementation, and evaluation. Second, in the marketing strategy planning process, SMPN 8 applies five marketing elements to promote the school. Third, the evaluation of marketing strategies at SMPN 8 Tanjungbalai is carried out at the end of the PPBD implementation period and documented in the form of an accountability report. Fourth, there are some problems with the marketing strategy at SMPN 8 Tanjungbalai in the 2022-2023 academic year. This is due to the lack of work motivation and teamwork of the organizing committee for new student admission activities.